The Role of Nizamiyah in the Development of Early Islamic Education - Romzi, Moh; Musthofa, M Lutfi; Noviyanti, Shobihatul Fitroh (Universitas Al-Amien Prenduan, 2024)
This research aims to examine the role of Nizamiyah in the development of Islamic education in the early period. Nizamiyah, as an Islamic educational institution founded in the 11th century by Nizam al-Mulk, has an important role in disseminating knowledge and educating Muslim scholars and scholars. This research uses the research library method by analyzing various relevant literature and historical sources, including manuscripts, books, journal articles and other scientific works. Through this qualitative approach, the research seeks to provide a comprehensive picture of Nizamiyah's contribution to intellectual and educational development in the history of Islamic civilization. The research results show that Nizamiyah not only functions as an educational center, but also as a center for the dissemination of ideologies and thoughts that have a wide influence in the Islamic world.